Feeding the Insatiable Beast: Education Technology and Digitization in Special Collections Libraries and Archives - Warren, Kellee E. (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2024)
This exploratory essay foregrounds the extraction and enclosure cycle between education technology (ed-tech) vendors and public academic special collections and archives departments. Education technology vendors, subsidiaries of academic publishers, often approach special collections libraries and archives with offers to digitize collections through services that McLaughlin et al. (2023) describe as open wrapping or freemium proposals. Since there seems to be no turning back, information professionals in public academic settings should, among other solutions, encourage decision-makers to negotiate preservation and conservation of physical archival materials. Drawing from the literature on commons practices, this essay introduces the concept of reciprocal relations to agreements between cultural heritage institutions and ed-tech companies. A reciprocal approach would disrupt the extraction and enclosure cycle and highlights the professional’s role as a steward of cultural heritage collections with an understanding that digitization is not preservation. Further, it would compel private sector companies to invest in the public sector instead of simply extracting public resources for profit.